The Effectiveness of Touch Math on Improving Early Mathematics Ability of Kindergarten Children with Mild to Borderline Intellectual Functioning in an Inclusion Classroom - Khalifa, Ayman Gamal; Saad, Mourad Ali Eissa (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
Touchmath®, also known as Touchpoint, is a multi-sensory method that involves visual, auditory, and tactile learning, and it can be used effectively with children with disabilities. It has successfully solved addition and subtraction problems with a single digit and two digits, specifically for children with disabilities. Six children participated. A multiple baseline design was used. The Test of Early Mathematics Ability was employed. The findings revealed that the touch math training program effectively improved the Early Mathematics Ability of each participant. All six children were found to be successful at the end of the teaching session compared to the baseline. The finding that Touchmath® showed positive effects based on a direct teaching approach in improving the Early Mathematics Ability of kindergarten children with mild to borderline intellectual functioning and their typically developing peers in an inclusion classroom is effective, sustainable, generalizable, and socially valid in teaching basic addition skills to students with mild intellectual disabilities in general education classrooms, conforms to other research conclusions in the literature.